Microencapsulation of Crude Folic Acid Extract from Chayote (Sechium edule Jacq. Swartz) with Ionic Gelation Method - Johana Novita Paulina Purba; Herla Rusmarilin; Zulkifli Lubis (Indonesian Food and Nutrition Progress, 2019)
Chayote is a plant which grow and develop throughout the year, contains of  93 mcg/100g folic acid. The aim of this research was to determine the ratio of sodium alginate with pectin and CaCl2 concentration coating to produce microcapsules of crude folic acid extract. Four phases of study was done, namely the manufacture of folic acid extract, manufacture of microcapsules with ionic gelation, analysis of folic acid content in the microcapsules, and the analysis of folic acid after storage of one week. Folic acid extract was made by maceration using alcohol 70% at pH 6, preparation of the microcapsules was using sodium alginate with pectin and folic acid was analysed using HPLC. Folic acid extract showed antioxidant activity of 98,1% with folic acid of 0,16 mg/kg. Microencapsulation of folic acid extract results showed the highest antioxidant activity was formed in alginate ratio of  70% to 30% pectin and CaCl2 concentration of 0.1 M i.e.  62.77 mg/kg. Folic acid is an antioxidant, highest antioxidant value folic acid was analyzed,  treatment was in alginate ratio of 70% to 30% pectin and CaCl2 concenration at 0.1 M i.e. 3.06 mg/kg, after one week at room temperature is became 2.39 mg/kg.